2006
DOI: 10.2106/jbjs.e.00550
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis in Adult Spinal Deformity Following Multisegmental Instrumentation and Arthrodesis

Abstract: The prevalence of pseudarthrosis following long arthrodesis with use of modern segmental spinal instrumentation for the treatment of spinal deformity in adults was 17%, and the clinical outcome in these patients can be negatively affected by the pseudarthrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 13 publications
0
91
4
Order By: Relevance
“…The average number of levels fused was 6.08 segments (range [4][5][6][7][8] in the L5 group and 6.09 (range 4-9) in the sacrum group with no statistical difference. The upper instrumented vertebra (UIV) was T9 in 2 patients, T10 in 11 patients, T11 in 3 patients, T12 in 3 patients, and L1 in 5 patients in the L5 group.…”
Section: Operative Proceduresmentioning
confidence: 83%
See 1 more Smart Citation
“…The average number of levels fused was 6.08 segments (range [4][5][6][7][8] in the L5 group and 6.09 (range 4-9) in the sacrum group with no statistical difference. The upper instrumented vertebra (UIV) was T9 in 2 patients, T10 in 11 patients, T11 in 3 patients, T12 in 3 patients, and L1 in 5 patients in the L5 group.…”
Section: Operative Proceduresmentioning
confidence: 83%
“…It has generally been accepted that the pseudarthrosis rate is higher when the fusion is extended to the sacrum than stopping fusion at L5 [8,9]. Higher rates of pseudarthrosis may be associated with a less rigid fixation method.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that may have contributed to the failure of sacral screw fixation, such as inadequate sacral bone purchase, inappropriate direction of the screw or depth of the screw insertion, osteoporotic sacral bone stock and excessive load resulting from a long fusion lever arm above the sacrum [11]. Multiple studies have demonstrated that sacral screw fixation not only has a high complication rate, but also has a poor outcome with eventual fixation failure when S1 pedicle screws are used alone without supplemental fixation [4,5,9,17]. To overcome these problems, alternative fixation techniques, such as transiliac bars and iliac post bolts were used.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of the lumbosacral region has been frequently complicated with problems such as non-union and implant failure. Many studies have shown a high pseudarthrosis rate and poor outcome associated with fixation failure when stand-alone S1 screw constructs were used [4,5,9,17]. Therefore, supplemental augmentation options for S1 screws have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical failures, including proximal junctional complications (PJCs) and pseudarthrosis, represent the most frequent type of complication following ASD surgery, with an incidence of 3.7-37 % [4][5][6][7][8][9][10][11][12][13][14][15][16]. The incidence of proximal junctional kyphosis (PJK) in patients with ASD has been reported to range from 17 to 41 % [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%